Intimate relationships - Miller, Rowland S.; Perlman, Daniel; Brehm, Sharon S. (Boston : McGraw-Hill Higher Education, 2007)
Presents the key findings on intimate relationships, the major theoretical perspectives, and some of the controversies in the field. This book illustrates the relevance of close relationship science to readers' everyday lives, encouraging thought and analysis. It includes coverage of online dating, fMRI studies of love, and mate poaching
t pt. 3. Friendship and intimacy -- 7. Friendship -- The nature of friendship -- Attributes of friendships -- The rules of friendship -- Friendship across the life cycle -- Infancy -- Childhood -- Adolescence -- Young adulthood -- Midlife -- Old age -- Differences in friendship -- Gender differences in same-sex friendships -- Individual differences in friendship -- For your consideration -- Chapter summary -- 8. Love -- A brief history of love -- Types of love -- The triangular theory of love -- Romantic, passionate love -- Companionate love -- Styles of loving -- Individual differences in love -- Attachment styles -- Age -- Men and women -- Does love last? -- Why doesn't romantic love last? -- So, what does the future hold? -- For your consideration -- Chapter summary -- 9. Sexuality -- Sexual attitudes -- Attitudes about casual sex -- Attitudes about same-sex sexuality -- Cultural differences in sexual attitudes -- Sexual behavior -- Premarital sex -- Sex in committed relationships -- Monogamy -- Sexual desire -- Preventing pregnancy and sexually transmitted infections -- Sexual satisfaction -- Sexual frequency and satisfaction -- Sex and relationship satisfaction -- Interdependency theory and sexual satisfaction -- Sexual communication -- Communicating desire -- Sexual communication and satisfaction -- Sexual aggression -- For your consideration -- Chapter summary. pt. 4. Relationship issues -- 10. Stresses and strains -- Relational evaluation -- Hurt feelings -- Ostracism -- Jealousy -- Two types of jealousy -- Who's prone to jealousy? -- Who gets us jealous? -- What gets us jealous? -- Responses to jealousy -- Coping constructively with jealousy -- Deception and lying -- Lying in close and casual relationships -- Lies and liars -- So, how well can we detect a partner's deception? -- Betrayal -- Individual differences in betrayal -- The two sides to every betrayal -- Coping with betrayal -- Forgiveness -- For your consideration -- Chapter summary -- 11. Power -- Power and interdependency theory -- Sources of power -- Types of resources -- The process of power -- The outcome of power -- The two sides of power -- For your consideration -- Chapter summary -- 12. Conflict and violence -- The nature of conflict -- What is conflict? -- The frequency of conflict -- The course of conflict -- Instigating events -- Attributions -- Engagement and escalation -- The demand/withdraw pattern -- Negotiation and accommodation -- Dealing with conflict : four types of couples -- The outcomes of conflict -- Ending conflict -- Can fighting be good for a relationship? -- Violence and abuse in relationships -- The prevalence of violence -- Types of couple violence -- Gender differences in partner violence -- Correlates of violence -- The rationales of violence -- Why don't they all leave? -- Violence in premarital relationships -- For your consideration -- Chapter summary. pt. 5. Losing and enhancing relationships -- 13. The dissolution and loss of relationships -- The changing rate of divorce -- The prevalence of divorce -- U.S. divorce rates in comparative perspectives -- Why has the divorce rate increased? -- The predictors of divorce -- Levinger's barrier model -- Karney and Bradbury's vulnerability-stress-adaptation model -- Results from the PAIR Project -- Results from the Early Years of Marriage Project -- People's personal perceptions of the causes of divorce -- Specific factors associated with divorce -- The road to divorce -- Breaking up with premarital partners -- Steps to divorce -- The aftermath of separation and divorce -- Individuals' perspectives -- Relationships between former partners -- Children whose parents divorce -- For your consideration -- Chapter summary -- 14. Shyness and loneliness -- Shyness -- Loneliness -- Measuring loneliness -- How does it feel to be lonely? -- Does loneliness matter? -- Who's lonely? -- Loneliness across the lifespan -- Possible causes and moderators of loneliness -- Inadequacies in our relationships -- Changes in what we want from our relationships -- Causal attributions -- Interpersonal behaviors -- Coping with loneliness -- What helps people feel less lonely -- Loneliness as a growth experience -- For your consideration -- Chapter summary -- 15. Maintaining and repairing relationships -- Maintaining and enhancing relationships -- Staying committed -- Staying content -- Repairing relationships -- Do it yourself -- Preventive maintenance -- Marital therapy -- In conclusion -- For your consideration -- Chapter summary -- References -- Credits -- Name index -- Subject index.
Rev. ed. of: Intimate relationships / Sharon S. Brehm ... [et al.]. 3rd ed. c2002.
Includes bibliographical references (p. R1-R86) and indexes.
Keywords: Family life education; Interpersonal relations